The psychological influencing factors for the elderly in using mobile applications and the mechanism of user experience - Jin, Shining (Frontiers in Psychology, 2025)
ObjectiveThis study is purposed to assess the user experience factors of elderly mobile applications from the cognitive psychology perspective and establish a comprehensive evaluation index system for the elderly-friendly experience of mobile applications.MethodsThe research subjects were the elderly. Their basic information, mobilephone usage experience, and demands for elderly-friendly experience were collected via questionnaires. The questionnaire design with a focus on the cognitive capabilities of the elderly as well as their emotional responses. Factor analysis was employed to process the questionnaire data, and three main factors were extracted: perceivability, operability, and comprehensibility. Additionally, the actual usage of two elderly-friendly mobile applications (WeChat and Toutiao Big Font Version) was evaluated through task tests. The task tests involved tasks such as mode switching, information viewing, and completion of specific operations.ResultsThe research findings demonstrate that perceptibility, operability, and comprehensibility are the principal factors affecting the mobile application experience of elderly users. Specifically, factors such as adjusting the font size of the interface, increasing the line spacing and character spacing of paragraph text, and providing images and text descriptions on the interface have a significant impact on the user experience. For instance, larger fonts and clear icon designs can significantly enhance the information perception ability of the elderly and reduce visual fatigue. Simple gesture operations and sufficient response time contribute to improving operability and resolving the operational difficulties resulting from the elderly’s motor skill limitations. Furthermore, the research also discovered that the age of elderly users have varying degrees of influence on the evaluation indicators of elderly-friendly design.ConclusionThis study, starting from the cognitive psychology perspective, proposes a scientific evaluation framework for elderly-friendly design, emphasizing the significance of considering the cognitive abilities and emotional needs of elderly users in the design process. The research results provide a theoretical foundation for the design and improvement of mobile applications, facilitating the enhancement of the usage experience and satisfaction of elderly users. Future research can further expand the sample range, conduct long-term follow-up studies, and integrate emerging technologies to optimize elderly-friendly design.